2001
DOI: 10.1038/sj.mp.4000883
|View full text |Cite
|
Sign up to set email alerts
|

Variability of 5-HT2C receptor cys23ser polymorphism among European populations and vulnerability to affective disorder

Abstract: Substantial evidence supports a role for dysfunction of brain serotonergic (5-HT) systems in the pathogenesis of major affective disorder, both unipolar (recurrent major depression) and bipolar. 1 Modification of serotonergic neurotransmission is pivotally implicated in the mechanism of action of antidepressant drugs 2 and also in the action of mood stabilizing agents, particularly lithium carbonate. 3 Accordingly, genes that code for the multiple subtypes of serotonin receptors that have been cloned and are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
84
2
3

Year Published

2005
2005
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 27 publications
4
84
2
3
Order By: Relevance
“…However, in our study, this polymorphism was significantly associated with PD in the total sample of patients with or without affective comorbidity (Maron et al, 2005b). Previously, a possible role for the Cys23Ser polymorphism was suggested in major depression and bipolar disorder (Lerer et al, 2001). Thus, this polymorphism may have nonspecific links to the comorbid phenotypes of PD, but its actual impact on the predisposition to PD remains unclear.…”
Section: -Ht Receptor Genescontrasting
confidence: 62%
“…However, in our study, this polymorphism was significantly associated with PD in the total sample of patients with or without affective comorbidity (Maron et al, 2005b). Previously, a possible role for the Cys23Ser polymorphism was suggested in major depression and bipolar disorder (Lerer et al, 2001). Thus, this polymorphism may have nonspecific links to the comorbid phenotypes of PD, but its actual impact on the predisposition to PD remains unclear.…”
Section: -Ht Receptor Genescontrasting
confidence: 62%
“…Two out of four studies found an increased frequency of the serine variant, indicating that this variant may be associated with major depression (Frisch et al 1999;Lerer et al 2001;Holmes et al 2003;Kö ks et al 2006). 5-HT2C receptor RNA undergoes adenosine-to-inosine RNA modification.…”
Section: -Ht2c Receptormentioning
confidence: 99%
“…In a second step, to assess whether AAO variation reflected the underlying genetic heterogeneity in BP, we examined the relationship of the HTR2C (cys23-ser) polymorphism (on chromosome Xq24) with EO-BP (cutoff of 16 years) in a subsample of BP patients previously reported by our group, 5 including 625 BP (of whom 66 were EO-BP) and 829 controls, recruited in eight collaborative centers (Athens, Bonn, Brussels, Edinburgh, Jerusalem, Milan, Sofia, Zagreb). All subjects were assessed by using criteria identified at standard diagnostic interviews, according to the DSM-IV.…”
mentioning
confidence: 99%
“…5,7 We performed logistic regression analyses to evaluate the effect of the 'diagnosis status' (EO-BP, BP with AAO > 16 years and control subjects) and the 'center' as predictors of the dependent variable (alleles/Ser23 carrier status), permitting to determine the significance of the diagnosis, controlled for the potential confounding effect of center. A significant association emerged with an excess of HTR2C Ser23 allele (23.8%) in EO-BP patients compared to controls (14.4%) (P = 0.004; OR = 2.1, CI (1.3; 3.4)) and BP with AAO > 16 (16.5%) (P = 0.039; OR = 1.7, CI (1.02; 2.9)).…”
mentioning
confidence: 99%
See 1 more Smart Citation